BALNEOTHERAPY IN AN EXTREMELY RARE CONDITION - PATTERSON-LOWRY SYNDROME - Gergana Gecheva-Fermendzhieva; Radko Radev; Miroslav Marinov (Peytchinski Publishing, 2019)
Purpose: The purpose of this case report is to show one of the rarest syndromes such as that of Patterson - Lowry and to prove that with a wide variety of treatment procedures, physiotherapy and rehabilitation speciality could improve patients' subjective complaints and restore the basic functions of the locomotor system in rare syndromes such as that of the two brothers represented in this report. Materials and Methods: The methods of physiotherapy and rehabilitation offered by Pavel Banya MC were used, as well as the methods of kinesiotherapy. Results: Improvement of patient's subjective complaints. Conclusion: Balneotherapy procedures have a beneficial effect on patients with rare diseases, not only through their analgesic action but also through the professionalism and the hope that experienced rehabilitators give patients and their families.